Systematic literature review on methodology and manufacturing process of personalized tablet using selective laser Sintering technology - Kamsani, Nurul Huda; Hasan, Muhammad Shamsuri; Chatterjee, Bappaditya D.; Haris @ Harith, Muhammad Salahuddin (Universitas Gadjah Mada, 2022)
3-dimensional printing (3DP) technology has garnered interests as a novel candidate for future pharmaceutical manufacturing. Since the first drug product (Spritam®) has been approved for commercialization by the Food and Drug Administration (FDA), there has been an enormous opportunity for printing custom drugs using 3DP. Many 3DP methods have been documented for pharmaceutical applications in the literature. However, selective laser sintering (SLS) printing remains the least studied for pharmaceutical applications. There are many advantages and challenges in adopting an SLS method to fabricate personalized medicines, such as accurate, cheaper, and simpler ways to configure dosing for certain patient groups. In this study, we systematically reviewed all available literature investigating the technique of personalized printlets using SLS printing, and further discussed the method used in its process. A systematic searching strategy was performed in Scopus, PubMed, and Google Scholar databases using predetermined search strings. Of the 122 articles, only eight articles completely met the inclusion criteria, and they were subsequently used for data synthesis. The results showed that the printing process, spectrophotometry analysis, thermal analysis, X-ray powder diffraction and characterization of the printlet were the vital parameters in the printing method, leading to potential pharmaceutical applications in personalized medicine.